PENGEMBANGAN MODUL BAHASA INDONESIA BERMUATAN NILAI KARAKTER KEBANGSAAN BAGI MAHASISWA PGSD - Subekti, Tabah (Profesi Pendidikan Dasar, 2016)
The research aims to develop module of bahasa which combined by national character. Background of this study is there’s not yet any module of bahasa which combined by national character, in the other side Indonesia needs teacher who able to teach and guide the children with national character to tighten the children’s nationality. By using this product, we hope that the student of elementary school teacher education (candidate of teacher) will able to teach and guide the children with national character. The research was supported by the expert in each field. The research divided become four step which called four-D (1) define; (2) design; (3) develop; and (4) disseminate. But, the duration of the research is only one year, so it caused the research only able to achieve third level (develop). The product of this research is a module of bahasa combined by national character which ready to used by lecturer in elementary school teacher education. Object of the research are the student of elementary school teacher education (candidate of teacher) in University of Muhammadiyah Magelang, Central Java. The result of the study described that development of module bahasa is done effectively. It can be seen from the lecturers and students respond who had helped by the module.